Hidden barriers and phylogeographical divergence in the central Cerrado: a comparative and predictive analysis - Silva, Luana Maria Deoclécio da [UNESP]; Bonatelli, Isabel A S; Amaral, Danilo T; Franco, Fernando F; Moraes, Evandro M (Oxford University Press (OUP), 2025)
Abstract Biogeographical barriers can limit gene flow between populations of different species, promoting species differentiation at the community level on a regional scale. Comparative phylogeography reveals how co-distributed species respond to shared historical events, including hidden barriers. These barriers resulted from past environmental changes, and although they do not have obvious physiographic features, they leave persistent genetic marks on populations. Here, we investigated the long-term east–west phylogeographical break in the Cerrado domain by reusing genetic data and examining correlated traits and climate variables. We employed Bayesian approaches to infer evolutionary events and assess the temporal congruence of east–west divergence among plant and animal species. We used predictive classification approaches to interrogate what biotic traits and environmental features can predict this east–west phylogeographical structure. Our results indicate that plants exhibit synchronous east–west divergence during the Pleistocene, while animals show multiple divergence pulses coinciding with Neogene and Pleistocene events. Taxonomy and biotic variables related to dispersal and connectivity significantly influenced the species’ responses to the east–west break. Our results suggest that the modern east–west disjunction shared by taxa of the central Cerrado is linked to hidden historical barriers, as well as to the intrinsic responses of organisms to biological diversification processes in this region.